Digital literacy content in the operational curriculum in Early Childhood education - Tafrihah, Tafrihah Tafrihah; Utanto, Yuli; Pristiwati, Rahayu (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
Abstract: The objective of this research is to assess the requirements for digital literacy within the curriculum currently employed, this research employs a qualitative approach, specifically utilizing a phenomenological methodology, the focus of this research is on the stakeholders of Tarbiyatul Athfal Bulumanis Kidul Kindergarten schools, the data collection process encompasses measures to delimit the research scope, gather information through methods such as observation, structured and unstructured interviews, documentation, visual materials, and the development of protocols for recording information, the data analysis employs a flow analysis model procedure involving three concurrent streams of activities, namely: the analysis process comprises three stages: 1) data reduction, 2) data presentation (utilizing data displays), and 3) conclusion drawing and verification. The research’s outcomes encompass an analysis of Vision, Mission, and Goals, as well as an analysis of the digital literacy curriculum in kindergarten schools; the objectives of this research encompass the following aspects: 1) the rationale for implementing the digital literacy content curriculum in kindergarten schools; 2) an analysis of the digital literacy needs among kindergarten teachers; and 3) the competencies to be cultivated through the adoption of a curriculum incorporating digital literacy in kindergarten schools.